Tracing the influence of stakeholders of the Nusantara masjid architecture - Mahyuddin, Izzat Asyraf; Abdul Rahim, Zaiton; Mohd Nawawi, Norwina (IOP Publishing, 2017)
Masjids or mosques were built across the Malay Archipelago or the Nusantara, as a statement on the rise and strengths of the Islamic community since the arrival of Islam in the 1300s. As the latest religion to the South-East Asia after Hindu- Buddhist, the mass often discusses the form and make of the masjid but seldom question who’s who constitutes the design and the rigmarole of masjids. This paper aim at identifying the stakeholders of masjid architecture of Nusantara through analysing the involvement of stakeholders from historical and primary data, covering the process of initiation, through masjid construction including the conceptions and perceptions on the factors influencing the architecture of the masjid. The paper intents to demystify the sole responsibility of the architect in designing masjid of Nusantara region and places the will of Islam as the religion of initiation and stakeholders, whom are the rulers, scholars and common Muslims, as the Ummah, the reason of its make and form it is today.